Instagram and Body Image: Factors of Reification among Adolescent Girls in Spain - Martínez Pérez, Natalia; Cuenca Orellana, Nerea; Dueñas Mohedas, Sonia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research studies the use of Instagram and its relationship with the construction of body image in adolescent girls. Firstly, we analyse the representations conveyed by the network and the gender discourses it articulates in order to identify what kind of strategies -visual and linguistic- are used by the most popular influencers to understand the discourses on corporeality. The structural-semiological content analysis of the five Instagram profiles of the most followed influencers in Spain by the so-called Z generation sheds light on gender stereotypes and roles, reflecting on the prevention of the phenomenon of reification and self-reification.